Assessing male involvement in childcare and associated factors among fathers of below two in Toke Kutaye district, Central Ethiopia, 2024: a community-based cross-sectional study - Ganfure, Gemechu; Darega, Jiregna; Kitila, Latera Debebe (Frontiers in Public Health, 2025)
BackgroundMale involvement in child care is increasingly acknowledged as a crucial factor for promoting positive health and developmental outcomes for children, particularly during the critical early years of life. In Ethiopia, low male participation in child-rearing exacerbates public health issues, including high neonatal and under-five mortality rates. This study examines the prevalence and factors associated with paternal involvement in child care among fathers of children under 2 years in Toke Kutaye District, Central Ethiopia.MethodsA community-based cross-sectional study was conducted from January 28 to February 16, 2024. A total of 605 fathers with children under 2 years were randomly selected for interviews. Data on male involvement in child care were collected using a structured questionnaire. Data were entered using Epi-data version 3.1 and analyzed using SPSS version 26. Bi-variable and multivariable logistic regression analyses were performed, applying adjusted odds ratios (AOR) with 95% confidence intervals (CI) to assess statistical significance, with a p < 0.05. Descriptive statistics were also computed and presented using text, charts, and tables.ResultsThe study found that 36.7% of fathers exhibited good involvement in childcare practices. While a majority contributed financially (55.6%) and engaged in play (55.4%), significantly fewer fathers participated in essential caregiving activities like feeding (27.3%) or seeking healthcare during illness (17.1%). Multivariable analysis identified significant predictors of paternal involvement: completing secondary education (AOR = 5.24, 95% CI: 2.64–10.38), having male children (AOR = 1.69, 95% CI: 1.094–2.62), first birth order (AOR = 5.66, 95% CI: 2.79–11.45), and fewer family size (AOR = 4.82, 95% CI: 2.58–9.016).ConclusionThis study underscores the limited yet essential role of fathers in child care within the Toke Kutaye District, revealing a need for targeted interventions to enhance paternal engagement. Promoting educational initiatives could serve as a strategy to foster deeper paternal participation in child-rearing practices, ultimately contributing to improved health and developmental outcomes for children.